Impact of combined vaginal group B Streptococcus screening (culture and rapid PCR) in pregnant women on neonatal morbidity and mortality - Maëlig Abgral; Léonie Albersammer; Julie Carrara; Christelle Guillet-Caruba; Alexandra Benachi; Daniele De Luca; Rafik Ben Ammar; Nadège Bourgeois-Nicolaos; Alexandre J. Vivanti (Journal of Infection and Public Health, 2025)
Background: Vaginal colonization by group B Streptococcus (GBS) in pregnant women is a major risk factor for early-onset neonatal infection, by vertical transmission during birth. Current guidelines recommend universal screening via vaginal swab and culture in the third trimester for antibiotic prophylaxis. Since 2013, the Antoine Béclère maternity hospital has offered combined screening for GBS carriage using culture at the third trimester and PCR on vaginal swabs in the delivery room. The primary aim was to assess the added value of PCR in culture-negative or unscreened women. Methods: This observational, retrospective, single-center study involved full-term deliveries between Jan 1, 2015, and Dec 31, 2020, in a type III perinatal unit (Clamart, France). All women at 35–38 weeks’ gestation (WG) were offered vaginal culture screening. PCR was performed in the delivery room if culture was negative or not done. Results: 15,013 patients gave birth to 15,337 newborns ≥37 WG; 14,863 women (99.0 %) were screened. Among 11,415 women with vaginal culture, 1416 (12.4 %) were positive. 3448 (23.0 %) were not screened by culture. PCR at birth identified 621 additional GBS cases (4.1 %): 327 (2.2 %) in unscreened women and 294 (1.9 %) with prior negative culture. No neonatal GBS infections were observed. There were 4 cases (0.02 %) of postpartum endometritis. Conclusion: Intrapartum PCR identified 2.2 % additional cases in unscreened women and 1.9 % missed after prior negative culture. This rapid and effective method appears feasible for routine use.